2017
DOI: 10.1021/acs.chemmater.7b00586
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Flow Synthesis of Pt1–xRuxNanoparticles: Comparative Phase Diagram Study of Nanostructure versus Bulk

Abstract: The thermodynamic stability of nanocrystals is different from bulk systems, and nanoscale phase diagrams are to a large degree unknown. Here we present a systematic investigation of the Pt1-xRux phase diagram through supercritical flow-synthesis of Pt1-xRux nanoparticles across the entire compositional range. The synthesis was done in stoichiometric steps of 0.1 using an ethanol-toluene mixture as solvent at 450°C and 200 bar. The products were characterized by high resolution synchrotron powder X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
(149 reference statements)
0
5
0
Order By: Relevance
“…This is just as true for materials in novel morphologies such as thin films and nanoparticles as it is for bulk materials. Recent work has shown that there are interesting examples of alloy compositions at which the phases that are stable at the nanoscale are not the same as those that are most stable in the bulk. This observation opens an avenue to development of new materials with properties at the nanoscale that could not be predicted on the basis of those of the bulk. Pursuing this opportunity requires methods for identifying phases and finding phase boundaries in alloy materials with morphologies that are not amenable to phase determination with traditional diffraction based methods.…”
Section: Introductionmentioning
confidence: 99%
“…This is just as true for materials in novel morphologies such as thin films and nanoparticles as it is for bulk materials. Recent work has shown that there are interesting examples of alloy compositions at which the phases that are stable at the nanoscale are not the same as those that are most stable in the bulk. This observation opens an avenue to development of new materials with properties at the nanoscale that could not be predicted on the basis of those of the bulk. Pursuing this opportunity requires methods for identifying phases and finding phase boundaries in alloy materials with morphologies that are not amenable to phase determination with traditional diffraction based methods.…”
Section: Introductionmentioning
confidence: 99%
“…This signal may be assigned to the reflection of the (101) planes of the hcp phase, i.e., the phase in which pure ruthenium typically crystallizes. Probably, ruthenium, or more likely a Ru-rich hcp phase, segregates at 500 °C. , These results suggest that the PMMA template triggers the low-temperature reduction and crystallization of the porous HEA-based particles and simultaneously hinders metal dealloying at high annealing temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…in 2017. 72 They used absolute ethanol as a solvent (reducing agent) at 200 bar and 450 °C. A mixture of Pt(acac) 2 (acac = acetylacetonate) and Ru(acac) 3 in an ethanol-toluene solution was mixed with the supercritical ethanol and passed through a reactor heated at 450 °C.…”
Section: Flow Syntheses Of Solid–solution Alloy Npsmentioning
confidence: 99%